Comparison of net GHG emissions between separated system and crop-swine integrated system in the North China Plain. (15th April 2017) - Li, Zhejin; Sui, Peng; Wang, Xiaolong; Yang, Xiaolei; Long, Pan; Cui, Jixiao; Yan, Lingling; Chen, Yuanquan
Abstract: Agriculture causes 10–12% of global GHG (CO2, CH4 and N2 O) emissions. GHG emissions from Chinese agriculture have been estimated at 819.97 Mt CO2 -equivalence (CO2 -eq); among them, total annual GHG emissions from the production of grain and livestock have been estimated at 374 Mt CO2 -eq and 445 Mt CO2 -eq, respectively. Because of food demand, food production has intensified, resulting in the separation of crop production and livestock rearing. This separation has increased the application of outside resources and agricultural waste, aggravating GHG emissions and other ecological and environmental problems. This research attempts to mitigate GHG emissions by improving soil carbon sequestration of crop production and decreasing emissions from swine-rearing waste. Net GHG emissions (NGHGE) between an integrated system and a separated system are compared in this study from a life-cycle perspective. The causes of different GHG emissions between these two systems are analyzed and mitigation strategies are proposed. The results show that the NGHGE of crop-swine integrated and separated systems were 24, 917.95 kg CO2 -eq/ha/yr and 27, 732.70 kg CO2 -eq/ha/yr, respectively, for 215 head of pigs. The integrated system reduced GHG by 1381.33 kg CO2 -eq/yr mainly due to the recycling and reuse of pig manure in croplands. Meanwhile, the integrated system increased soil carbon storage by 35.92% compared with the separated system, although it increased soil CH4 and N2 O emissions. In conclusion, these results indicate that through a series of methods, such as recycling agricultural waste, the integrated system can reduce net GHG emissions by 10.15% compared with separated systems. Although much work remains to adopt the integrated system to reduce GHG emissions, the crop-swine integrated system should be given priority to mitigate anthropogenic net GHG emissions. Graphical abstract: Highlights: NGHGE between separated system and crop-swine integrated system were compared in North China Plain. Both GHG emissions and carbon sequestrations were taken into consideration. The two systems exhibited different results in the trials. Integrated system reduced GHGs mainly due to recycled and reused of agricultural wastes and increased soil carbon storage. Integrated system can realize reduction of net GHG emissions compared with separated system.